Myths in Philippe Le Guillou’s initiatory triptych: about the new enchantment of the world through myths and great heroes - Lasticova, Adriana (Amaltea. Revista de Mitocrítica, 2025)
The aim of this paper is to contribute to the study of the novels of the contemporary French writer Philippe Le Guillou. Thanks to the methodological basis of thematicism and the prism of mythocriticism combined with comparative literature, we outline here the main signs of the longing for a new enchantment of the world through the insertion of myths in his initiatory triptych formed by the novels Livres des guerriers d’or (1995), Les sept noms du peintre (1997) and Douze années dans l’enfance du monde (1999). The aim of the work is above all to reflect the author’s personal strategy based on returning to the great stories with the great mythological or biblical heroes and thus underlining the ancestral wisdom and the relevance of the imaginary cultural heritage of the West as well as the spiritual dimensions of life.